A zebrafish intelectin ortholog agglutinates both Gram-negative and Gram-positive bacteria with binding capacity to bacterial polysaccharide. (August 2016) - Chen, Lei; Yan, Jie; Sun, Weiping; Zhang, Yan; Sui, Chao; Qi, Jing; Du, Yijun; Feng, Lijun
Abstract: Intelectins are glycan-binding lectins found in various species including cephalochordates, urochordates, fish, amphibians and mammals. But their detailed functions are not well studied in zebrafish which is a good model to study native immunity. In this study, we cloned a zebrafish intelectin ortholog, zebrafish intelectin 2 ( zITLN2 ), which contains a conserved fibrinogen-related domain (FReD) in the N-terminus and the unique intelectin domain in the C-terminus. We examined the tissue distribution of zITLN2 in adult zebrafish and found that zITLN2 was expressed in various organs with the highest level in intestine. Like amphioxus intelectins, zITLN2 expression was upregulated in adult zebrafish infected with Staphylococcus aureus with the highest expression level at 12 h after challenge. Recombinant zITLN2 protein expressed in E. coli was able to agglutinate both Gram-negative and Gram-positive bacteria to similar degrees in a calcium-dependent manner. Furthermore, recombinant zITLN2 bound lipopolysaccharide (LPS) and peptidoglycan (PGN) comparably. Our work on zITLN2 provided further information to understand functions of this new family of lectins and the innate immunity in vertebrates. Highlights: An zebrafish intelectin ortholog, zITLN2 with a fibrinogen-related domain and a unique intelectin domain was characterized. The zITLN2 is widely expressed with highest level in intestine and upregulated after challenge of Staphylococcus aureus. Recombinant zITLN2 binds both LPS and PGN to similar degrees and agglutinates both Gram positive and negative bacteria.